Developing Effective Teacher Performance - Jones, Jeff. , Jenkin, Mazda dan Lord, Sue (SAGE, 2006)
Improving and maintaining staff performance is an important and often difficult responsibility for school leaders and senior teachers. Designed to help teachers who manage others, this practical book offers guidance on diagnosing ineffectiveness, supporting ineffective teachers, and using appropriate strategies when support isn't enough.